THE LINGUOCULTURAL STUDY OF THE CONCEPT OF “PATIENCE” - Akbarova Zukhro Akmaljonovna; Mamasolieva Nozima , Khaydaralieva Saodat (EPRA International Journal of Research and Development (IJRD), 2022)
The article provides information on the linguocognitive and linguocultural study of the concept and discusses the verbalization of the concept of “patience” in the Uzbek language.